A short history of anti-rheumatic therapy - V. Analgesics - P. Marson; G. Pasero (PAGEPress Publications, 2011)
The pharmacological treatment of pain has very ancient origins, when plant-derived products were used, including mandrake extracts and opium, a dried latex obtained from Papaver somniferum. In the XVI and XVII centuries opium came into the preparation of two compounds widely used for pain relief: laudanum and Dover's powder. The analgesic properties of extracts of willow bark were then recognized and later, in the second half of the XIX century, experimental studies on chemically synthesized analgesics were planned, thus promoting the marketing of some derivatives of para-amino-phenol and pyrazole, the predecessors of paracetamol and metamizol. In the XX century, nonsteroidal anti-inflammatory drugs were synthesized, such as phenylbutazone, which was initially considered primarily a pain medication. The introduction on the market of centrally acting analgesics, such as tramadol, sometimes used in the treatment of rheumatic pain. is quite recent.